Health Status of Rural Girls - Madhuri Inamdar; Sameer Inamdar; N. L. Sachdeva (Medsci Publications, 2011)
Background- In most of the developing countries, the girl child is ill fed and undernourished. 1 Quite often the root cause of malnutrition among girls is not so much the lack of food as the lack of access to food. Thus undernourished girls who grow into undernourished women perpetuate the intergenerational undernourishment cycle.2 Aims and objectives- 1- To assess the health status of female child, 2- To compare the health status of female child with that of male child and to determine if gender discrimination exists. Material and Methods- Sixteen villages were selected by stratified sampling. Altogether 470 household were selected by systematic sampling method. Only those households which had at least one male and one female child ( 0-14 Yrs.) were included in the study. Observations- 44.63% of girls below 5 years of age were found to be malnourished in comparison to 15% of boys in the same age group ( P< 0.001). The percentage of stunted male children ( 6-14Yrs.) was 14.78 while that of female children was 33.89. ( P< 0.001). While 3/4th of the boys received complete treatment, it was only 2/3rd in case of girls. Conclusion- Malnutrition was pronounced in girls as compared to boys.